Application of universal design in healthcare built environment - Rahim, Asiah; Abd Samad, Nur Amirah (Kulliyyah of Architecture and Environmental Design, 2010)
Accessibility to buUt environment are increasing needed due to the increasing number of people surviving to older ages which are adding to the numbers of person with disabilities. The need of frait and firm to elderly persons for accessibJe built environments are similar to those of the group generally describe as persons with disabilities. The main purpose of this research is to audit accessibility of buildjng facilities for the disabled persons~ elderJy and chUdren, at hospitaJ buHdings, and Hospitar Putrajaya has been selected for this research. The methodo'ogy used is based on table research, and simulation on the users of the facilities, observations and photographs. The access audit is carrred out together with students of the fifth year Architecture from Jnternational Islamic University Malaysia and experts of access audit. The findings and recommendations from the study will give insights to the problems faced by the disabled persons, thus enable the owner of the building to upgrade the facUities provided in their building to serve the need of the target group. The recommendation can also be used as guidennes to des;gners, building owners and people who involved in building industry